Investigation of Antimicrobial Susceptibilities and Resistance Genes of Campylobacter Isolates from Patients in Edirne, Turkey - Canan Eryıldız; Nermin Sakru; Gulcan Kuyucuklu (Tehran University of Medical Sciences, 2022)
Background: We aimed to determine the susceptibility of Campylobacter isolates obtained from patients to various antimicrobial agents and to investigate some related antimicrobial resistance genes. Methods: Fifty-six Campylobacter isolates obtained from fecal specimens by conventional methods at the Trakya University Health Center for Medical Research and Practice, Department of Medical Microbiology in Edirne, Turkey, from 2017-2017 were included. Antimicrobial susceptibilities were investigated by the gradient strip test method, and species determination was made by multiplex polymerase chain reaction (mPCR). The presence of the erm(B) gene and tet(O) gene was investigated in all isolates by PCR. DNA sequence analysis was performed to detect the presence of mutations in the 23S rRNA positions 2074 and 2075 in five isolates, including two erythromycin resistant isolates. The gyrA gene mutation was investigated by the mismatch amplification mutation assay (MAMA)-PCR. Results: In 54 C. jejuni isolates, resistance to erythromycin was 3.7%; to tetracycline, 59.3%; and to ciprofloxacin, 74.1%. Phenotypically, the tet(O) gene was detected in 33 tetracycline-resistant isolates, but no erm(B) gene was found in any of the Campylobacter isolates. As a result of the DNA sequencing, it was found no mutations in the 23S rRNA gene at the 2074 and 2075 positions. The gyrA mutation was observed in all 41 ciprofloxacin resistant Campylobacter isolates. Conclusion: Among the antimicrobial agents tested, ciprofloxacin had the highest resistance rate, and erythromycin had the lowest. Antimicrobial resistance in Campylobacter increased significantly compared with previously studies in our region as well as in the entire world. Monitoring the resistance to antimicrobial agents used to treat Campylobacter infections is important in determining empiric antimicrobial treatment.